2011
DOI: 10.1073/pnas.1011995108
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected pathway of the allosteric transition in hemoglobin

Abstract: Large conformational transitions play an essential role in the function of many proteins, but experiments do not provide the atomic details of the path followed in going from one end structure to the other. For the hemoglobin tetramer, the transition path between the unliganded (T) and tetraoxygenated (R) structures is not known, which limits our understanding of the cooperative mechanism in this classic allosteric system, where both tertiary and quaternary changes are involved. The conjugate peak refinement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 48 publications
10
57
0
1
Order By: Relevance
“…This quaternary change is followed by primarily tertiary relaxation to reach the fully developed R state. Significant tertiary changes after the quaternary transition are in accord with what has been predicted for hemoglobin (27). Once the twisting is completed, agonist unbinding (here L-glutamate) from the orthosteric site results in a large reorientation or tilting of the extracellular β-sandwiches in the outward direction, which drags the β 1 -β 2 loop into the up position.…”
Section: Resultssupporting
confidence: 68%
“…This quaternary change is followed by primarily tertiary relaxation to reach the fully developed R state. Significant tertiary changes after the quaternary transition are in accord with what has been predicted for hemoglobin (27). Once the twisting is completed, agonist unbinding (here L-glutamate) from the orthosteric site results in a large reorientation or tilting of the extracellular β-sandwiches in the outward direction, which drags the β 1 -β 2 loop into the up position.…”
Section: Resultssupporting
confidence: 68%
“…2 with α ¼ − logðsÞ∕ logðcÞ; the values reported in Table 1 yield α ¼ 0.33 and 0.81 for HbA and HbYQ, respectively. In the case of HbA, the difference between our estimate and the value of α ¼ 0.17 determined by TR-OA data (23) may be traced to the proposed stepwise character of the R-T allosteric transition (10,14,26). Following this idea, Cammarata et al (13) proposed that TR-WAXS essentially monitors a first step of the R-T transition of HbA (namely the αβ dimers rotation and translation), while TR-OA monitors a second slower step associated with a more localized reorganization around the active site; accordingly, the transition states explored by TR-WAXS and TR-OA spectroscopy are not the same (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Spectroscopic and crystallographic studies have shown that the αβ dimers rotation is associated with a rearrangement around Trp37(C3)β, located in the so-called "hinge" region. In discussing their conjugate peak refinement calculations, Fischer et al (14) pointed out that the transition of His97(FG4)β gliding over Thr41(C6)α at the switch interface occurred in the main Q 2 phase of the allosteric conformational change. How do the distal side mutations introduced in HbYQ affect the α 1 β 2 interface, where the quaternary transition is associated to the largest changes?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many powerful enhanced sampling techniques have been developed to efficiently harvest computational trajectories that include barrier crossings or other rare events (e.g., Refs. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, many of these methods are limited by requiring a priori knowledge of reaction coordinates, one or few pathways to completion, or only several metastable minima.…”
Section: Introductionmentioning
confidence: 99%